Introduction to Various Professions Through Psychoeducation for Children of Migrant Workers in Malaysia - Jati Fatmawiyati; Ninik Setiyowati; Retno Sulistiyaningsih; Roni Setiawan; Nur Hafif; Shohenuddin Shohenuddin (Universitas Nurul Jadid, 2025)
Children of Indonesian migrant workers in Malaysia face limited access to formal education due to administrative and citizenship constraints. This situation leads to minimal career literacy, restricting their knowledge about various professions in society. As a result, these children often struggle with motivation and confidence in exploring career options that align with their potential and aspirations. This community service program aims to enhance the career literacy of migrant workers’ children through psychoeducational interventions. The method involves structured career psychoeducation sessions that introduce various professions, career pathways, and skill development opportunities. The program includes interactive discussions, career visualization activities, and hands-on workshops conducted in community learning centers where migrant workers' children receive informal education. Data collection was carried out through pre- and post-intervention assessments, including observations, interviews, and questionnaires to measure changes in career awareness and motivation. The results indicate that psychoeducation significantly improves children's understanding of different professions and the educational paths required to pursue them. Moreover, the program boosts their confidence in career planning and reduces anxiety about their future employment prospects. By providing psychological support and structured career guidance, this approach helps children develop skills and aspirations aligned with their career interests. Thus, psychoeducation serves as an effective strategy in supporting the children of Indonesian migrant workers in Malaysia, enabling them to unlock their full potential and prepare for the workforce more confidently and competently.